Conhecimento científico e o saber popular sobre os moluscos nos terreiros de Candomblé de Recife e Olinda, estado de Pernambuco. - Silva, Maria Conceição da (2006)
Studies about the relation "Popular and the Scientific Knowledge" will be able to contribute to rescue the re-significance of Social, Teach function and Politics of the Educative spaces. Based on this principle, this work had as main objective to understand the relations between the popular and scientific knowledge, with emphasis in the use of the molluscs in the Candomblé s terreiros from Recife and Olinda, Pernambuco state. The methodology from characterizes as qualitative research, using the following methodological procedures: participant comment (Phenomenology), through interviews with Babalorixás and Yalorixás; documentary research; pedagogical workshops; it collects and registers of the molluscs species and survey with the children s, that frequent the Candomblé s terreiros, about Nature conceptions. Of the seven interviewed (4 Babalorixás and 3 Yalorixás), all affirm the importance of the molluscs in the Candomblé`s rituals, mainly the 4 more sacred molluscs, Cauri, Ibi, Aruá and the Ikoto. The mollusc (Cypraea sp.) it is the most sacred, representing force, power and wisdom. The shell is used to Ifá, divination, to the Oxalá and all the type of initiation in Candomblé`s religion. In the activities with childrens, 22 in the total, the one that more was distinguished was the pedagogical workshop with the drawings, which had expressed some forms of harmonic trees, with the presence of the sun, flowers and birds demonstrating affective and/or religious bows with "Nature mother". In a general way, in its majority a Romantic and Naturalistic Conception were evidenced about the Nature. The mollusk marine, gastropods mainly, are important commercially its use as food, in the manufacture objects, adornments and medicines to the calcium base. The use and it collects of these animals of indiscriminate form, from the Pernambuco state currently there are 6 threatened gastropod s species of extinguishing. Currently, the EtnoConservation of natural resources has been seen as a positive reply of the local populations, to neutralize natural and economic losses in the environment. In the specific case of the Candomblé`s terreiros he is being developed a continuous work of Environment Education with Babalorixás and Yalorixás and this work comes to contribute for a project s proposal, in the Candomblé`s terreiros from Recife and Olinda, for the molluscs conservation, a time that these can be substituted by other natural and/or symbolic elements in the sacred religion rituals.